Melanie Klein: a psychobiographical study - Espinosa, Marianna J (Rhodes University, Faculty of Humanities, Department of Psychology, 2008)
The objective of psychobiography is a better understanding of individuals, and psychobiographical case studies add meaning and value to research (Runyan, 1988a). Melanie Klein was chosen for this study through a purposive sampling method due to her contributions to the discipline of psychology, which placed her in a distinguished position regarding twentieth century psychoanalysis. Furthermore, no other psychobiography has been written on Klein. The primary aim of this study was to present the reader with a basic description of her life, and a secondary aim was to accomplish an in-depth description of Klein within her social and historical context. Due to these aims and the nature of psychobiography, it may be said that this is a qualitative study based on a single case method, described as explorative and descriptive. Data was analysed according to Huberman and Miles' (1994) approach which consists of data reduction, display and verification. This study was guided by Levinson's (1996) theory of Adult Development in Women. The theory allowed for an in-depth description of Klein's experiences and social and historical contexts by merely illuminating her life. Finally, it may be said that this study contributed to the limited amount of psychobiographical research in South Africa.
Keywords: Klein, Melanie; Psychology -- Biographical methods; Psychoanalysis